Analisis Pengetahuan Mitigasi Bencana Abrasi untuk Calon Guru Sekolah Dasar - Putri, Kuntum Sharfina; Noviana, Eddy; Guslinda, Guslinda (ARZUSIN, 2024)
This study aims to describe the abrasion disaster mitigation knowledge of prospective elementary school teachers, namely FKIP UNRI elementary school teacher education students. The research subjects were elementary school teacher education students who had taken disaster mitigation courses in semester 2. The type of research is quantitative descriptive research. The data collection method in this study is in the form of a description test totaling eight questions consisting of 4 dimensions of knowledge. The data analysis technique in this study uses descriptive statistics in the form of calculating knowledge scores from 1-4 and then calculating the percentage. The results showed that the overall abrasion disaster mitigation knowledge of prospective elementary school teachers was in the sufficient category with an average of 71.31%. The results of each dimension of knowledge, namely the factual knowledge dimension in the sufficient category with an average value of 75.69. Conceptual indicators are in the insufficient category with an average value of 66.67. Procedural indicators get an average value of 72.92 which is in the sufficient category and metacognitive indicators get an average value of 69.68 in the insufficient category.